Zebra Cabs vs Uber : waking up the South African Metered taxi industry - Bowen, Amanda (London : Wits Business School, 2016)
In August 2016, Ana Bonanni, head of Zebra Cabs, a South African metered taxi service based in Gauteng, had just finished a radio interview with Cape Talk journalist, Barry Bateman. The interview had focused on the disruption caused by the entry of e-hailing ride service, Uber, into the fragmented South African metered taxi industry, and whether traditional metered taxi services could survive. Zebra Cabs had implemented massive technological and vehicle changes in order to compete. However, Bateman had planted a seed of doubt in Bonanni's mind. Would the Zebra Cabs business model eventually disappear in favour of Uber? How could she ensure that Zebra Cabs weathered the Uber storm?
Originally published in Bowen, A. (2016). Zebra Cabs vs Uber: Waking up the South African metered taxi industry. WBS-2016-12. Johannesburg: The Case Centre, Wits Business School.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Bonanni, Ana; Bateman, Barry -- (Journalist); Zebra Cabs; Uber (Firm); Taxicab industry -- South Africa